UJI PRAKTIKALITAS ALAT PERAGA MAGNET SEBAGAI MEDIA PEMBELAJARAN IPA FISIKA SMP - Hafiz Suhendra; Zulirfan '; Hendar Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The porpose of this research to measure the practicality level of experimental devices of magnetic as media physics learning of junior high school. The device consisting of 8 pieces, those are magnetic levitation, magnetic resonance, magnetic field energy, test properties of magnetic material, detector properties of magnetic material, magnetic induction rotaty machine, compolar motor 1, compolar motor 2 and students experimental guide. Data collected by giving a questionnaire of practicality to teachers and students. There were 5 science teachers and 30 students of junior high school have participated in this research. Data were analyzed descriptively to determine the level of the experimental device practicaility. The result of data analysis this research found the level of practicality is in high and very high category and the assessment of the experimental guide practice is very high category. Based on data analysis, it can be concluded that the experimental device of magnetic are practical and feasible to be used as learning media physics of junior high school.Keywords: practicality level, magnetic experimental devices, magnetic field